2013
DOI: 10.1111/irv.12205
|View full text |Cite
|
Sign up to set email alerts
|

The substantial hospitalization burden of influenza in central China: surveillance for severe, acute respiratory infection, and influenza viruses, 2010–2012

Abstract: BackgroundPublished data on influenza in severe acute respiratory infection (SARI) patients are limited. We conducted SARI surveillance in central China and estimated hospitalization rates of SARI attributable to influenza by viral type/subtype.MethodsSurveillance was conducted at four hospitals in Jingzhou, China from 2010 to 2012. We enrolled hospitalized patients who had temperature ≥37·3°C and at least one of: cough, sore throat, tachypnea, difficulty breathing, abnormal breath sounds on auscultation, sput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
100
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(121 citation statements)
references
References 32 publications
18
100
3
Order By: Relevance
“…We used data from an active, population‐based surveillance system to assess epidemiological and clinical characteristics of hospitalized children with influenza. Our results are consistent with our recent disease burden estimation, which found that influenza was associated with an estimated 2021 SARI hospitalizations per 100 000 during 2010–2011 and 2349 per 100 000 during 2011–2012 among children aged <5 years10 and other studies outside China 12, 13. In this study, we observed the low birth weight and living with someone who smokes cigarettes in the household were independent risk factors for increased odds of influenza among children with SARI.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We used data from an active, population‐based surveillance system to assess epidemiological and clinical characteristics of hospitalized children with influenza. Our results are consistent with our recent disease burden estimation, which found that influenza was associated with an estimated 2021 SARI hospitalizations per 100 000 during 2010–2011 and 2349 per 100 000 during 2011–2012 among children aged <5 years10 and other studies outside China 12, 13. In this study, we observed the low birth weight and living with someone who smokes cigarettes in the household were independent risk factors for increased odds of influenza among children with SARI.…”
Section: Discussionsupporting
confidence: 93%
“…Surveillance was conducted in Jingzhou, Hubei Province, in three general hospitals and one pediatric hospital as previously described 10. All patients admitted to a surveillance hospital were screened by nurses and physicians for SARI and were considered eligible if the SARI case definition was met within 24 hours of hospital admission.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data from Kuala Lumpur consist of laboratory-confirmed influenza, and we show that influenza B virus accounts for 26% of all influenza cases, suggesting a considerable national burden of disease, which is consistent with previously reported data indicating that influenza B virus accounted for 9 to 48% of confirmed influenza cases in Malaysia from 2006 to 2014 (4,6,20). Our study also showed an overwhelming burden of influenza B virus cases in young children, consistent with previous studies globally (3,(21)(22)(23)(24). Active coordination of surveillance efforts in sentinel clinics and hospitals, including the standardization of patient and epidemiological data collected, is needed to effectively monitor influenza disease dynamics in Malaysia.…”
supporting
confidence: 89%
“…The World Health Organization's (WHO) global standards for influenza surveillance are used by many countries 8, 9, 10, 11. Severe acute respiratory infection (SARI) surveillance intends to capture hospitalized influenza‐associated severe respiratory illness cases and uses a case definition—either recommended by WHO or country‐specific—to identify severe presentations of influenza‐associated respiratory disease 12.…”
Section: Introductionmentioning
confidence: 99%